Quality of life outcomes following 1 year encouragement of pelvic floor muscle exercise among urinary incontinence women living in the community - Chawawisuttikool, Jitapa; Sriboonreung, Thanyaluck; Yankai, Araya; Parameyong, Arisa (Journal of Associated Medical Sciences, 2021)
Background: Urinary incontinence (UI) is a silent problem affecting women’s health. This problem causes lower self-confidence to participate in various activities. Pelvic floor muscle exercise (PFE) is the first recommended for treatment of UI. Adherence to PEF is the key to success in maintaining continence. However, no studies have supported the effect of sustaining PFE continually on the symptoms of UI and the quality of life (QoL) in the long term. Objectives: This study aimed to investigate the effect of the 1-year encouragement of PFE on UI symptoms and the quality of life among incontinence women living in the community. Materials and methods: Thirty-four women with UI aged between 50-70 years were invited in this study. The women were interviewed for the UI variables including the ability to hold urine, the frequency and amount of UI, feeling urgency to urinate, the frequency of urination during the daytime and nighttime. Additionally, the King’s health questionnaire (KHQ- Thai version) was used to measure the quality of life. The UI variables and KHQ were measured at baseline, 3rd, 6th, 9th and 12th months of the intervention. PFE program was provided to participants after baseline measurement and encouraged to perform continually and consistency for 1 year. Descriptive statistics, one-way repeated ANOVA and Friedman test were used to analyze the data. Results: At the end of program, 24 women (92.3%) had no problems with urinary control. In part of the frequency and the amount of stress UI, all of them were completely improves (100%). In terms of the symptoms associated with urged UI such as the feeling urgency to urinate, most of them had no hustle during urination (80.8%). The frequency of urination was reduced, all of them had less than 5 times urination during the day. The severity of symptoms associated with UI was significantly different compared to baseline. In addition, the KHQ score for all items was lower, indicating a higher QoL when compared to baseline. Conclusion: Longterm promoting of PFE was effective for the improvement of UI and significantly increased the QoL among incontinence women living in communities.